Synthesis and self-aggregated nanostructures of hydrogen-bonding polydimethylsiloxane. Issue 28 (9th July 2021) - Chen, Senbin; Wu, Yanggui; Wang, Huiying; Zhu, Bengao; Xiong, Bijing; Binder, Wolfgang H.; Zhu, Jintao
Abstract : Reversible lamellae (LAM), hexagonally packed cylinders (HPC), body-centered cubic spheres (BCC) and disordered micelles (DIM), are realized by tuning the nature of H-bonding moieties (Ba, TAP, HW), the molecular weight of PDMS, and the temperature. Abstract : Gaining control over assembled nanostructures is an important aspect in nanotechnology and materials. Compared to specific directional interactions, self-aggregation of clusters driven by the forces of hydrogen-bonding (H-bonding) polymers, constitute a novel and simple strategy toward the tuning of nanostructures. In this work, we first demonstrate the precise synthesis of tailored polydimethylsiloxane (PDMS) at their α-ends bearing a series of H-bonding moieties ( e.g., barbiturate (Ba), 2, 4, 6-triaminopyrimidine (TAP) and Hamilton wedge (HW)), using a robust copper(i )-catalyzed azide–alkyne cycloaddition (CuAAC) reaction. Complete end group functionalization is proven by NMR and matrix-assisted laser desorption/ionization time of flight mass spectrometry (MALDI-MS) methods. Self-aggregated H-bonds are indeed formed in the melt state from the obtained H-bonding PDMS, evidenced by temperature dependent solid-state 1 H MAS NMR. Subsequent small angle X-ray scattering (SAXS) studies unveil a profound picture of nanostructures, including lamellae (LAM), hexagonally packed cylinders (HPC), body-centered cubic spheres (BCC) and disordered micelles (DIM). We found that these morphologies are influenced by the molecular weight of the PDMS (1200, 5800 and 11 300 g mol −1 ), as well as by the nature of H-bonding moieties ( e.g., Ba, TAP, HW), proving that both the immiscibility parameter and the volume fraction between nonpolar PDMS and polar H-bonding moieties determine the final structures. Moreover, we also demonstrate a thermally reversible order–disorder transition (ODT) in the observed nanostructures, induced by the H-bonding self-aggregation as observed by temperature-dependent SAXS investigations. The strategy to engineer nanostructures to form the cluster and aggregation of H-bonding polymers is significant, providing new insights to control the supramolecular polymer chain organization and phase separation effects.